The effect of extensions in constructing a Hebraic word (comparative study with the Arabic language) - Safieh, Wahid (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aims to focus on the changes that happen to a Hebraic word when adding extensions. We discovered that adding those extensions affects the rhythm changes, the voice order changes, deleting and moving it, and sometimes return it to its base, also adding the extensions plays a role in changing the meaning. We done all this work by comparing with the Arabic language, so the worth of this work become greater, because the two languages belongs to the same language family.